Hanseníase em menores de 15 anos: caracterização sociodemográfica e clínica dos casos notificados em um munícipio hiperendêmico do Maranhão (2010-2019) - SILVA , Francisca Jade Lima de Andrade (2021)
The occurrence of leprosy in children under 15 years of age represents an important epidemiological indicator that reflects the expansion and severity of the disease. The objective was to analyze the sociodemographic and clinical profile of notified cases of leprosy in children under 15 years of age in the city of São Luís - MA, from 2010 to 2019. This is a descriptive, retrospective study with a quantitative approach. The population consisted of all cases of leprosy in children under 15 years of age reported in the Notifiable Diseases Information System (SINAN). For the complementary data extracted from the Complementary Protocol for Diagnostic Investigation of Leprosy Cases in Children Under 15 Years (PCID), a sample was obtained for 122 cases. Data collection was carried out from November 2020 to January 2021. Data were produced in the EPI-INFO program, version 7 (CDC - Atlanta), from descriptive statistics, expressed in absolute and relative frequencies. In the period analyzed, they reported 826 cases of leprosy in children under 15 years of age, which corresponds to 8.9% of the total cases reported in the general population. The municipality of São Luís was classified with hyperendemic parameters throughout the historical series, detection rates above 10 cases/100 thousand inhabitants in the population aged zero to 14 years. Regarding sociodemographic aspects, leprosy occurred more frequently in children aged between 10 and 14 years (60.29%), male (51.09%), mixed race (69.59%), who attended between the 5th and 8th grade of incomplete primary education (39.58%) and who lived in the state capital (71.91%). In the analysis of clinical aspects, cases with multibacillary operational classification predominated (62.71%), borderline clinical form (54.24%), 0 to 5 skin lesions (74.45%), 0 to 2 affected nerves (83 .23%) and zero degree of physical disability at diagnosis (78.89%). About bacilloscopy, less than half of those notified perform the exam (46.28%). As for the mode of entry, new cases (93.70%), detected by spontaneous demand (46.38%) and referrals (37.34%) prevailed. With regard to complementary clinical data from the PCID (n=122), a higher percentage of cases that received the diagnosis of the disease after more than one year of symptom onset (41.80%) was found. Regarding current symptoms, more than half of the children analyzed had not undergone previous treatment (57.38%), and among those who had undergone previous therapeutic followup (n=51), about 41.91% treated the symptoms of leprosy as a disease of skin caused by fungus (41.91%). Considering leprosy in the family, most cases had contact in the family environment (59.02%), with at least one sick person (62.50%). The study shows high rates of detection, late diagnosis, family history, detection of serious and transmissible forms, low active search for cases, failures in control actions and difficulties in making the diagnosis, indicating active transmission and maintenance of the disease's severity in the region. analyzed. Thus, it is recommended the improvement of more specific measures to fight leprosy in children.